Unconditioned and conditioned responses to colour in the predatory coccinellid, Harmonia axyridis (Coleoptera: Coccinellidae) - Edward B. MONDOR (European Journal of Entomology, 2000)
We determined if mature ladybirds use colour to initially find suitable host plants. We also determined whether ladybird beetles are capable of associating characteristics such as colour with the presence of prey. Here, we show that the multicoloured Asian ladybird beetle, Harmonia axyridis, has a differential response to yellow compared to green colours. Naive ladybirds, of both sexes, make significantly more visits and spend more time on yellow vs. green coloured pillars. After pairing yellow and green colours with the presence or absence of aphid prey, ladybirds alter their foraging behaviour. Beetles conditioned to having food on both pillar colours exhibited the same responses as naive beetles, while beetles conditioned to only yellow or green pillars did not exhibit a preference for visiting or spending time on different colours. However, there was a trend towards females spending more time on pillar colours on which they received reinforcement, and males spending more time foraging on colours opposite to that which they were reinforced. Thus, H. axyridis is capable of responding to cues such as colour, and its foraging behaviour can be altered as a result of prior experience.